The dynamic impacts of alternative livestock sector intervention and spending options in Rwanda - Aragie, Emerta A.; Bahta, Sirak T.; Baltenweck, Isabelle; Enahoro, Dolapo K.; Karugia, Joseph T.; Thurlow, James; Warner, James (International Food Policy Research Institute, 2025)
This study evaluates the cost-effectiveness of various livestock interventions—feed, breeding, and health—and budget allocation strategies (balanced, feed-oriented, breeding oriented, and health-oriented) in the context of Rwanda’s economic and livestock systems. Using an economic and livestock systems integrated framework, the research highlights moderate yet sustained impacts on agricultural Gross Domestic Product (GDP) and significant improvements in the livestock sector. Overall, breeding interventions have the largest cumulative effect on agricultural GDP, while health measures, particularly dewormers, yield long-term gains in livestock productivity. Under the balanced scenario, breeding contributes significantly to both meat and milk sector GDP, while feed interventions show a smaller impact overall. The study also finds that biased spending scenarios lead to differing outcomes across livestock sub-sectors. Breeding-oriented spending boosts milk GDP initially, whereas health-oriented spending excels in meat production through reduced deaths and increased liveweight. By the end of the simulation period, a balanced investment strategy results in a 12.5 percent increase in meat yield and a 27 percent rise in milk yield, largely driven by breeding. Health interventions, particularly deworming, are crucial for sustained meat production, while improved feed mitigates mortality and supports stock growth. These results can support policy dialogue, such as the recently introduced Fifth Strategic Plan for Agriculture Transformation (PSTA 5), as policy makers seek to revitalize the livestock sector and enhance its resilience to future challenges.